Exercise, immune function and respiratory infection: An update on the influence of training and environmental stress. Issue 2 (8th December 2015) - Walsh, Neil P; Oliver, Samuel J
Abstract : This review outlines recent advancements in the understanding of athlete immune health. Controversies discussed include whether high levels of athletic training and environmental stress (for example, heat acclimation, cryotherapy and hypoxic training) compromise immunity and increase upper respiratory tract infection (URTI). Recent findings challenge early exercise immunology doctrine by showing that international athletes performing high‐volume training suffer fewer, not greater, URTI episodes than lower‐level performers and URTI incidence decreases, not increases, around the time of competition compared with heavy training. Herein we raise the possibility of host genetic influences on URTI and modifiable behavioural and training‐related factors underpinning these recent observations. Continued controversy concerns the proportion of URTI symptoms reported by athletes that are due to infectious pathogens, airway inflammation or as yet unknown causes and indeed whether the proportion differs in athletes and non‐athletes. Irrespective of the cause of URTI symptoms (infectious or non‐infectious), experts broadly agree that self‐reported URTI hinders high‐volume athletic training but, somewhat surprisingly, less is known about the influence on athletic performance. In athletes under heavy training, both innate and acquired immunity are often observed to decrease, typically 15–25%, but whether relatively modest changes in immunity increase URTI susceptibility remains a major gap in knowledge. With the exception of cell‐mediated immunity that tends to be decreased, exercising in environmental extremes does not provide an additional threat to immunity and host defence. Recent evidence suggests that immune health may actually be enhanced by regular intermittent exposures to environmental stress (for example, intermittent hypoxia training). Abstract : The February 2016 issue contains a Special Feature on the Effects of exercise on the immune system and metabolism coming into the Olympic year. The role of the immune system in exercise is complex and challenging. Too little exercise can depress the immune system. In contrast, too much exercise can also lead to a compromised immune system. This is a challenge that athletes face as they prepare for competition. Immunology & Cell Biology thanks the coordinators of this Special Feature ‐ Mark Febbraio and Graeme Lancaster ‐ for their planning and input.